2009
DOI: 10.1016/j.fuel.2007.07.029
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbon particle type in fly ashes on mercury adsorption

Abstract: Recent research has shown that certain fly ash materials produced in coal combustion for power generation have an affinity for the mercury compounds present in flue gases. However, the exact nature of Hg-fly ash interactions is still unknown and the different variables that influence mercury adsorption need to be identified. In this work the microscopic components of fly ashes derived from the combustion of different types of feed blends of different coal rank and mercury adsorption were investigated. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…A number of investigations have attempted to correlate Hg retention and oxidation with the content and characteristics of unburned carbon in raw fly ashes [15][16][17] and have found that, in general, Hg capture increases in fly ashes with a high carbon content [18]. However, the precise mechanisms by which the unburned carbon present in fly ash interacts with Hg species in gas phase are not yet well understood.…”
Section: Because the Different Modes Of Occurrence Of Hg Involve Diffmentioning
confidence: 99%
“…A number of investigations have attempted to correlate Hg retention and oxidation with the content and characteristics of unburned carbon in raw fly ashes [15][16][17] and have found that, in general, Hg capture increases in fly ashes with a high carbon content [18]. However, the precise mechanisms by which the unburned carbon present in fly ash interacts with Hg species in gas phase are not yet well understood.…”
Section: Because the Different Modes Of Occurrence Of Hg Involve Diffmentioning
confidence: 99%
“…Comparing to anisotropic carbon particles, the relation between isotropic carbon particles and mercury capture capacity is not so clear (Figure 8), even in high mercury concentration [17]. There is no obvious relationship between other petrology components (including other organic, glass, spinels, etc.)…”
Section: Relation Between Unburned Carbon Petrology Components and Mementioning
confidence: 95%
“…The porous carbon particle has a great specific surface area, so it can adsorb more mercury. Antonia et al investigated mercury adsorption performance of fly ash in high mercury concentration (about mg/m 3 ), and they also suggested that the relation between anisotropic carbon and mercury capture capacity is very clear [17].…”
Section: Relation Between Unburned Carbon Petrology Components and Mementioning
confidence: 99%
See 1 more Smart Citation
“…The major factors affecting mercury removal efficiency are composition of the fly ash, unburned carbon content, reactivity, and surface area [20,21]. For this study, the fly ash sample was collected at the outlet of the ESP from a Chinese pulverized coal boiler utilizing bituminous coal.…”
Section: Fly Ash Collectionmentioning
confidence: 99%